The short-term effects of laparoscopic sleeve gastrectomy on hematological parameters - Karaca, Fatih Can (My University, 2020)
Introduction: Sleeve gastrectomy (SG) surgery is an effective method for weight loss in obese individuals.The data on the effect of this surgical intervention on iron metabolism and hematological factors are limited.This study aimed to investigate the effects of SG surgery on iron and red blood cell-related parameters.Materials and Methods: The six-month follow-up data of 33 patients who underwent SG for obesity treatment were evaluated retrospectively in this study. Whole blood levels of hemoglobin, mean corpuscularvolume (MCV), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW-CV),and serum iron concentrations were evaluated.Results: Mean hemoglobin, MCHC, and RDCV levels did not show a significant difference compared to thebaseline and between months. Mean MCV levels significantly differed from baseline values at the end of thethird month. Serum iron levels were significantly higher on the 6-month follow-up visit.Conclusion: The findings suggest that the iron level and other iron-related hematological parameters of thepatients who underwent SG improved after the surgery.